Відносини капіталу в сфері вищої освіти як джерело руйнування інноваційного потенціалу України - Яковенко, Р. В.; Yakovenko, R.; Яковенко, Д. В.; Yakovenko, D. (Ексклюзив-Систем, 2018)
Досліджено специфіку виробничих відносин у сфері вищої освіти України, яка характеризується відносинами традиційного капіталу. The specifics of industrial relations in the sphere of higher education of Ukraine, characterized by relations of traditional capital, are investigated.
Capital relations in the field of higher education as a source of the destruction of Ukraine's innovative potential
Keywords: вища освіта; капітал; експлуатація; людський капітал; корупція; higher education; capital; exploitation; human capital; corruption